2009
DOI: 10.3399/bjgp09x420563
|View full text |Cite
|
Sign up to set email alerts
|

Direct access to diagnostic services

Abstract: However, even well developed evidencebased guidelines are often not used in day-today care (estimations range from 25-50%). There are different causes for clinical guidelines not being used, partly related to the guidelines themselves. For instance, some guidelines are written as a handbook on a clinical topic and not as a concise set of concrete recommendations for decisions in day-to-day practice. They often have too many recommendations, making it difficult for the user to identify the key-issues and most i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…51 The limited uptake of direct access by GPs highlights a need to engage GPs in the planning and implementation of new services. 427 Direct access may result in reduced waiting times from presentation to testing and treatment. 427 A review found that direct access to diagnostic tests allows GPs to manage a substantial number of patients who would otherwise have been referred to the hospital outpatient department.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…51 The limited uptake of direct access by GPs highlights a need to engage GPs in the planning and implementation of new services. 427 Direct access may result in reduced waiting times from presentation to testing and treatment. 427 A review found that direct access to diagnostic tests allows GPs to manage a substantial number of patients who would otherwise have been referred to the hospital outpatient department.…”
mentioning
confidence: 99%
“…427 Direct access may result in reduced waiting times from presentation to testing and treatment. 427 A review found that direct access to diagnostic tests allows GPs to manage a substantial number of patients who would otherwise have been referred to the hospital outpatient department. 428 Limited information is available on costing associated with increased access to diagnostics for GPs versus hospital-based access only.…”
mentioning
confidence: 99%
“…6 The second study (296 recruited) reported a positive outcome, 7 but this result was compromised by a number of serious methodological flaws, including an inadequate randomisation procedure, single blind design, and a 25% drop out rate (not included in the analyses). 8 Following the publication of these three trials in 2007, 4,6,7 some commentators still recommended the use valaciclovir for those with severe facial weakness, 9,10 despite the evidence of lack of effectiveness. Most recently, the Swedish study 5 has hopefully put the matter beyond doubt, with no evidence that valaciclovir was effective in the management of Bell's palsy.…”
Section: Doi: 103399/bjgp09x453756mentioning
confidence: 99%
“…After decades of little persuasive evidence, four randomised controlled trials, involving over 1800 patients, have recently been published, and their results allow much more robust conclusions regarding drug treatment of Bell's palsy. [4][5][6][7] Steroids definitely improve outcome, based on the results of two large primary care based trials which addressed this question. The Scottish Bell's palsy trial 4 included 551 patients recruited from primary care, and showed that 83% of patients treated with prednisolone within 72 hours of onset (50 mg/day for 10 days) had recovered compared to 63.6% who received placebo at 3 months (number needed to treat [NNT] = 6) and this result remained significant at 9 months (NNT = 8).…”
Section: Doi: 103399/bjgp09x453756mentioning
confidence: 99%
See 1 more Smart Citation